Genome Resource Draft Genome of Fusarium avenaceum, Strain F156N33, Isolated from the Atmosphere Above Virginia and Annotated Based on RNA Sequencing Data - Yang, Shu (Plant disease, 2022)
Fusarium avenaceum is a filamentous fungus commonly associated with plants and soil. It is a causal agent of Fusarium head blight (FHB) on maize and small-grain cereals and blights on other plant species, and is one of the very few fungal species known to have ice nucleation activity (i.e., it catalyzes ice formation). Here, we report the draft genome of the ice-nucleation-active F. avenaceum strain F156N33 isolated from the atmosphere above Virginia. The genome assembly is 41,175,306 bp long, consists of 214 contigs, and is predicted to encode 11,233 proteins, which were annotated using RNA-sequencing data obtained from the same strain